The Effect of Organization Culture, Leadership Style and Working Discipline on Job Satisfaction at the Ministry of Religious Affairs of The Bengkulu City - Zoniarti, Zoniarti; Mu'min, Halek; Edy Anan (West Science Business and Management, 2024)
This research aims to prove the influence of work culture, leadership, and discipline on employee satisfaction, The method used in this study is to use quantitative with explanatory research approach. The population uses employees of the Ministry of Religious Affairs of Bengkulu city, using a sample of 152 samples taken using side random. The results showed that b1 = 0.277: is the regression coefficient value of work culture variable X1 with a value of 0.323 (positive sign), b2 = 0.370 is the regression coefficient value of leadership variable X2 providing a value of 0.370 (positive sign), and b3 is the regression coefficient value of discipline variable X3 providing a value of 0.447 (positive sign). The test results using SPSS, where the significant level obtained is smaller, namely 0.000 from the standard, namely 5% or 0.05 and the comparison results between F_hitung≥F_tabel 58.692 ≥ 3.06, it can be concluded that there is a significant influence between variables X1 (work culture), X2 (leadership style), and X3 (work discipline), and Y (job satisfaction).